Effect of Green Roofs on the Thermal Environment of Prototype Broiler Houses - Maria Angela de Souza; Fernanda Campos de Sousa; Alex Lopes da Silva; Thauane Cordeiro Soares; Charles Paranhos Oliveira; Ricardo Brauer Vigoderis; Fernando da Costa Baêta; Ilda de Fátima Ferreira Tinôco (AgriEngineering)
The management of thermal environments in animal production facilities presents significant challenges, requiring continuous adjustments to meet animals’ physiological needs. This study evaluated the effects of green roofs on the thermal environment and comfort indices in small-scale poultry house prototypes, comparing facilities with and without green roof installations. The research tested various roof types (ceramic, fiber cement, and metal) combined with emerald grass (Zoysia japonica) green roof systems. Parameters measured included air temperature, relative humidity, internal roof surface temperature, Temperature and Humidity Index (THI), Black Globe Humidity Index (BGHI), Human Comfort Index (HCI), and Thermal Radiation Load (TRL) under both open and closed conditions. Results showed that green roofs reduced indoor air temperature by up to 2.4 °C in open prototypes and 10.6 °C in closed prototypes during peak heat periods. In combinations using green roofs with fiber cement tiles, internal roof surface temperature decreased by 24.0 °C in open prototypes and 27.0 °C in closed configurations. The implementation of green roofs resulted in THI reductions of 2.3 and 8.1 units in open and closed prototypes, respectively, BGHI decreases of 2.8 and 11.3 units, and TRL reductions of 21.0 W/m2 and 74.0 W/m2. HCI measurements confirmed improved thermal comfort conditions with green roof installations in both settings. This study concludes that green roofs effectively enhance the thermal environment by reducing bioclimatic indices during hot periods while maintaining stable conditions during cooler weather, thereby improving overall thermal comfort in animal facilities.